Understanding Experiences of Youth Growing Up with Anorectal Malformation or Hirschsprung's Disease to Inform Transition Care: A Qualitative In-Depth Interview Study - Nah, Shireen Anne; Ong, Caroline C. P.; Lie, Desiree; Marimuttu, Vicknesan Jeyan; Hong, Julian; Te-Lu, Yap; Low, Yee; Jacobsen, Anette Sundfor (European Journal of Pediatric Surgery, 2018)
Introduction The impact of anorectal malformation (ARM) or Hirschsprung's disease (HD) in children continues into adulthood despite early surgical correction. We aimed to explore the physical, social, and emotional impacts of these conditions on youth to inform best transition care strategies.Materials and Methods Eligible participants were those aged between 14 and 21 years who had undergone surgery for ARM/HD in our institution. We conducted one-on-one in-depth interviews to saturation using a question guide developed from literature review and clinician expertise. Deidentified transcripts were coded by four coders (two pediatric surgeons, one psychiatrist, and one qualitative expert) for major themes using a constant comparison approach. A theoretical model for understanding the transition experience was developed using grounded theory.Results Out of 120 patients identified as eligible, 11 youth (6 males) participated in the study. Interviews lasted from 50 to 60 minutes. Four major themes emerged: (1) social support (subthemes: family as core, friends as outer support), (2) cognitive and emotional change (subthemes: realization/recognition of illness, matching emotional response), (3) impact of physical symptoms (subthemes: adverse effects of abnormal bowel habits, gaining bowel continence control leading to overall feeling of control, need to keep disease private), and (4) healthcare providers (viewed as important information sources). Themes did not differ by gender.Conclusion Our model suggests that participants' understanding of bowel disease evolved over time with a “lightbulb” moment in preteens or early teens accompanied by increasing disease ownership and self-management. Clinicians should independently engage with patients in late childhood to address evolving emotional and information needs and encourage increasing autonomy. Future studies should explore communication approaches to meet transition needs of patients.
Keywords: adolescent; transition care; chronic illness; congenital; quality of life